Strategi Transformasi Digital untuk Meningkatkan Kinerja dan Layanan Publik pada Kantor Wilayah Kementerian Agama Provinsi Lampung - Fajri, Nurul (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2024)
This policy paper describes that in the digital era, digital transformation has become crucial for enhancing public performance and services. The Lampung Provincial Ministry of Religion (Kanwil Kemenag Lampung) needs to adapt by utilizing digital technology to improve efficiency, effectiveness, and service quality. This policy paper aims to formulate a comprehensive digital transformation strategy for Kanwil Kemenag Lampung to improve public performance and services. This policy paper employs a qualitative research method with literature studies, interviews, and observations. Data is analyzed descriptively to generate a contextual and applicable digital transformation strategy. The analysis results indicate five main pillars of digital transformation for Kanwil Kemenag Lampung: (1) Digital Infrastructure Development: Building a robust and integrated digital infrastructure to support public services; (2) Digital Application Development: Creating innovative digital applications to enhance internal process efficiency and public services; (3) Human Resource Capacity Enhancement: Improving the capacity of Kanwil Kemenag Lampung's human resources in using digital technology; (4) Data Governance Strengthening: Building effective data governance to ensure data security, integrity, and accessibility; and (5) Work Culture Change: Cultivating an adaptive, innovative, and public service-oriented work culture. The conclusion is that digital transformation of Kanwil Kemenag Lampung through the five main pillars can significantly improve public performance and services. Implementing this strategy will assist Kanwil Kemenag Lampung in providing faster, easier, more transparent, and accountable services to the public.